2023
DOI: 10.32920/ryerson.14656581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

International students in Canada: policies and practices for social inclusion

Abstract: Despite federal policy changes facilitating the recruitment and retention of international students in Canada, programming at Canadian universities is uneven and has created conditions for the population’s social exclusion. Canadian immigration policy has positioned international students as a desirable cohort of prospective immigrants, due to their age, economic potential, education, and official language skills. Canada’s 2014 International Education Strategy aims to double the number of international student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…The diversity of population we have Canada is a crucial asset to consider for this purpose. Cox (2014) argues that we should connect international students to "social capital," referring to "social resources within immigrants' ethnocultural or linguistics community" and provide them with "opportunities to access and interact with resources" in order to improve their settlement experiences (p.41). Gates-Gasse's study emphasizes the importance of developing social and community connections referencing the findings of a consultation forum arranged by Halifax Region Immigration Strategy in which it was revealed that 89% of international students who had "developed strong social and community roots" intended to settle in the province (2012, p. 278).…”
Section: Social Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of population we have Canada is a crucial asset to consider for this purpose. Cox (2014) argues that we should connect international students to "social capital," referring to "social resources within immigrants' ethnocultural or linguistics community" and provide them with "opportunities to access and interact with resources" in order to improve their settlement experiences (p.41). Gates-Gasse's study emphasizes the importance of developing social and community connections referencing the findings of a consultation forum arranged by Halifax Region Immigration Strategy in which it was revealed that 89% of international students who had "developed strong social and community roots" intended to settle in the province (2012, p. 278).…”
Section: Social Integrationmentioning
confidence: 99%
“…Flynn & Bauder (2013) identify a "major settlement service gap" during the "period of transition when migrant workers or students possess temporary status" which can be "anywhere from eight months to two years, immigrants are not eligible to receive government-funded settlement services" (p.9). Cox (2014) argues that "CIC settlement-funding model should be expanded that international students are eligible to use immigrant settlement services" because "the long-term economic intentions for international students should position them within the qualifying boundaries for CIC-funded settlement services" (p.79). The lack of settlement services could impact the transition of international students, and Belkhodja argues that "transition has an impact on integration" in the long term (2013, p. 4).…”
Section: Immigration Policy Makersmentioning
confidence: 99%
“…Our SPT perspective centers on practices that actors engage in, in which they use resources more or less effi ciently and equally through activities, such as (in this article) traveling. Earlier applications of SPTs to cycling, by Elizabeth Shove and others, 41 already give an idea of the usefulness of this perspective in understanding the coevolution of cycling and driving and rightly emphasize the complexity of the changes in collective travel choices that SPTs both highlight and analyze. Th e analytical focus on practices is important because more than by technology alone, resource use and equity are driven by people's behavior, their ways of doing.…”
Section: Section 2: Conceptual Approachmentioning
confidence: 99%
“…İlgili çalışmaları Kanada'nın, Almanya'nın ve Türkiye'nin göç ve eğitim politikası ve ülkeler arası karşılaştırmalı politikalara yönelik yapılan araştırmalar olarak sınıflandırmak mümkündür. Bu kapsamda Kanada'daki (Gravelle, 2017;Cox, 2014;Hynie, Korn ve Tao, 2016;Hynie, 2018;Hynie vd., 2019), Almanya'daki (Gesley, 2017;Korntheuer ve Damm, 2019;Vogel ve Stock, 2017) ve Türkiye'deki (Emin ve Coşkun, 2016;Kılıç ve Özkor, 2019;Özcan, 2018;Şimşek, 2019;Tanrıkulu, 2017;Tanrıkulu, 2018;Usta, Arıkan, Şahin ve Çetin, 2018) göçmenlerin veya mültecilerin eğitim süreçlerine ilişkin çeşitli çalışmaların yapıldığı tespit edilmiştir. Göç ve eğitim politikaları açısından ülkelerin karşılaştırmalı olarak incelendiği araştırmalara bakıldığında; Kanada ve Almanya'nın (Homuth, Will ve Maurice, 2020;Korntheuer vd., 2018;Pritchard, Korntheuer, Wilkinson ve Maehler, 2020), Kanada ve Türkiye'nin (Aydın, 2020;Kandemir, 2018) ve Almanya ve Türkiye'nin (İli, 2020) göç ve eğitim politikalarının karşılaştırmalı olarak değerlendirildiği görülmektedir.…”
Section: İlgili çAlışmalarunclassified
“…Yükseköğretim kademesinde ise öğrenciyi yalnızca bu kademeye değil, aynı zamanda mesleki yaşama adapte etmek amaçlanır. Bu amaç doğrultusunda Kanada'da üniversite eğitimi alan göçmen öğrenciler, ekonomik açıdan değerlendirilmekte ve vasıflı göçmenlerin yetiştirilmesine yönelik uygulamalar yapılmaktadır (Cox, 2014).…”
Section: Kanada'nın Eğitime Entegrasyon Politikalarıunclassified